Hollow hydrogel networks for temperature-controlled water fluidics. Issue 73 (24th August 2018) - Chen, Qing; Liang, Shumin; Song, Xiaodong; Naumov, Panče; Zhang, Lidong
Abstract : A simple, yet robust, reproducible and scalable method for direct conversion of sodium alginate (SA) films to multibranched hydrogel tubes (HTs) in "one-pot" reaction of buffered aqueous solution is reported. Abstract : We report the first example of a simple, yet robust, reproducible and scalable method for direct conversion of sodium alginate (SA) films to multibranched hydrogel tubes (HTs) in "one-pot" reaction of buffered aqueous solution. This method allows for construction of branched hollow HTs of any shape and arbitrary size, and enables further functionalization for application requirements.